BIONOMIC EQUILIBRIUM ANALYSIS HARVESTING BROOK TROUT - COHO SALMON FISHERY IN THE PRESENCE OF TOXICITY - Sari Gustiarto, Novia
In this model we discuss the bioeconomic harvesting of the Great Lakes predatory fisheries of Brook-Trout and Coho Salmon where both species are infected by some of the toxins released by several other species. Over-harvesting will destabilize the populations of these two fish in the oceans and possibly lead to an ecological disaster or the extinction of one or more fish species. While on the other hand, harvesting fish is one of the supporting economic activities for the people around the big lake. Therefore, how to model the predator prey equation to find a stable point between the number of fish populations and economic factors. The method used is to build a model that fits the conditions and factors that influence predator-prey interactions and then look at the stability of predator and prey growth using maple software and then look for bionomic balance to find the appropriate amount to be taken based on fishing costs. The model states that harvesting and toxicity have a big impact in decreasing the predator prey population, especially Coho Salmon as a predator. Even variations in the concentration of poison state that the higher the toxicity, the population of Coho Salmon decreases drastically. From an economic point of view, the higher the cost, the more likely it is to get Coho salmon with a high selling value.